2017
DOI: 10.1155/2017/3468276
|View full text |Cite
|
Sign up to set email alerts
|

Major Polymorphisms of Genes Involved in Homocysteine Metabolism in Malaria Patients in Ouagadougou, Burkina Faso

Abstract: This study analyzed the four main polymorphisms of the genes in homocysteine metabolism in malaria patients. Forty-two randomly selected subjects, diagnosed positive for Plasmodium falciparum, were included. The four genotypes were detected by real-time PCR using the MTHFR 677C>T, MTHFR 1298A>C, MTR 2756A>G, and MTRR 66A>G detection kit (Sacace Biotechnologies REF: T01002-96-S). The results revealed frequencies of 90% 677CC, 10% 677CT, and 00% 677TT for MTHFR C677T; 78.6% 1298AA, 19% 1298AC, and 2.4% 1298CC fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The homocysteinemia (12.6 µmol/L) found in the malaria negative controls of the present study is higher than the plasma concentration of homocysteine reported in Burkina (6.9 ± 1.3 µmol/L for men and 5.9 ± 1.9 µmol/L for women) [13] [14], and similar to the levels of 13.5 µmol/L found in Togo and 14.1 µmol/L in Benin [30]. In fact, it is well known that homocysteinemia varies according to methionine-rich diet or genetic polymorphisms of the enzymes involved in the homocysteine metabolism [14] [25]. A multidisciplinary approach thus fixing the food factor could better help to understand the influence of the infection with Plasmodium falciparum on the plasma concentration of homocysteine in Burkina Faso.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The homocysteinemia (12.6 µmol/L) found in the malaria negative controls of the present study is higher than the plasma concentration of homocysteine reported in Burkina (6.9 ± 1.3 µmol/L for men and 5.9 ± 1.9 µmol/L for women) [13] [14], and similar to the levels of 13.5 µmol/L found in Togo and 14.1 µmol/L in Benin [30]. In fact, it is well known that homocysteinemia varies according to methionine-rich diet or genetic polymorphisms of the enzymes involved in the homocysteine metabolism [14] [25]. A multidisciplinary approach thus fixing the food factor could better help to understand the influence of the infection with Plasmodium falciparum on the plasma concentration of homocysteine in Burkina Faso.…”
Section: Discussionsupporting
confidence: 67%
“…Mobilization of glutathione by the malaria parasite to resist oxidative stress promotes the accumulation of homocysteine in the host cell. Previous studies reported an association between human genetic factors and the progression to severe malaria with an increasing level of plasma Hcy [24] [25].…”
Section: Introductionmentioning
confidence: 95%
“…Sulfadoxine (sulfonamide) is an antibiotic that inhibits the metabolism of folic acid (vitamin B9). Folic acid is essential for Plasmodium development [15]. Plasmodium synthesizes folic acid in 2 enzymatic steps using dihydropteroate synthetase (DHPS) then dihydrofolate reductase (DHFR).…”
Section: Sulfadoxine-pyrimethamine Mechanism Of Actionmentioning
confidence: 99%